2019
DOI: 10.1111/adb.12808
|View full text |Cite
|
Sign up to set email alerts
|

Role of BRD4 phosphorylation in the nucleus accumbens in relapse to cocaine‐seeking behavior in mice

Abstract: Cocaine addiction is a chronic relapsing brain disorder characterized by compulsive drug seeking. Preliminary study suggested that bromodomain‐containing protein 4 (BRD4), an epigenetic reader protein, participates in cocaine‐induced reward and neuroplasticity. However, the exact role of BRD4 in cocaine addiction, particularly cocaine relapse, remains elusive. In this study, we found that BRD4 phosphorylation in the nucleus accumbens (NAc) was closely related to the maintenance of cocaine reinforcement and rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…In addition, a previous study showed that JQ1 could inhibit the expression of a key set of neuroplasticity‐related genes (i.e., Egr‐2, insulin‐like growth factor 2) in the anterior cingulate cortex of medial PFC and remote fear memory and fear generalization and response in a model of PTSD (Duan et al., 2020). JQ1 administration significantly decreased the expressions of Arc mRNA in the nucleus accumbens induced by cocaine (Guo et al., 2020). The chronic inhibition of Brd4 prevented the increased expression of Arc, c‐fos, FosB, and ΔFosB observed in a dyskinesia model of animals after levodopa administration (Figge & Standaert, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a previous study showed that JQ1 could inhibit the expression of a key set of neuroplasticity‐related genes (i.e., Egr‐2, insulin‐like growth factor 2) in the anterior cingulate cortex of medial PFC and remote fear memory and fear generalization and response in a model of PTSD (Duan et al., 2020). JQ1 administration significantly decreased the expressions of Arc mRNA in the nucleus accumbens induced by cocaine (Guo et al., 2020). The chronic inhibition of Brd4 prevented the increased expression of Arc, c‐fos, FosB, and ΔFosB observed in a dyskinesia model of animals after levodopa administration (Figge & Standaert, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CK2-mediated phosphorylation of a conserved acidic region in BRD4 dictates whether this region contacts with juxtaposed bromodomain (BD2) or an adjacent basic region, therefore determining if BD2 is free to bind acetylated-TF p53 (Wu et al, 2013). The same mechanism also applies in cocaine-seeking behavior and memory function in mice, as cocaine or neuronal stimulation induces the activation and binding of pBRD4 to the key gene promoter, which can be attenuated by CK2 blockade (Korb et al, 2015;Guo, 2020). Therefore, apart from modulating BRD4 bromodomains' interactions with chromatin, strategies targeting activated pBRD4 may represent an alternative and promising approach.…”
Section: Modulation Of Bromodomain and Extra-terminal Domain Protein Functions By Post-translational Modificationsmentioning
confidence: 99%
“…Increased phosphorylation of BRD4 in this acidic region because of decreased protein phosphatase 2A (PP2A) activity has been linked to triple-negative breast cancer (TNBC) progression (Shu et al, 2016). This phosphorylation event is also important for learning and memory, as well as normal brain functioning and drug addiction, as illustrated in mouse behavioral studies (Korb et al, 2015;Guo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%